Accelerated reliability and durability testing technology - Klyatis, Lev M. (Wiley series in systems engineering and management, 2012)
Learn how ART and ADT can reduce cost, time, product recalls, and customer complaints This book provides engineers with the techniques and tools they need to use accelerated reliability testing (ART) and accelerated durability testing (ADT) as key factors to accurately predict a product's quality, reliability, durability, and maintainability.